A Micro-trigeneration Geothermal Plant for a Smart Energy Community: The Case Study of a Residential District in Ischia. Issue 1 (March 2021) - Ceglia, F; Marrasso, E; Roselli, C; Sasso, M
Abstract: Improvements for islands sustainability subjected to strong anthropogenic pressures could be obtained by innovative solutions for energy supply by using local energy renewable sources. This paper analyses the possible benefits of a geothermal energy community, consisting of residential users, located in Ischia, an island of Naples in South of Italy. The proposed system is mainly based on an Organic Rankine Cycle plant interacting with a medium temperature geothermal source. This system satisfies both community's pure electric load and electricity requests of the electric-driven heat pumps for space conditioning and domestic hot water demands. The entire system and residential users were modelled and dynamically simulated by considering hourly electric, thermal/cooling and domestic hot water loads variation during three reference days for winter, summer and intermediate season. The proposed plant was compared to a traditional system in which the electricity to meet the total community's electric loads, is taken from the national power grid. The results highlight that the use of proposed system instead of traditional one allows to avoid 29.9 tons per year of CO2 emissions. Furthermore, this proposed system ensures the island-operation of community exploiting local renewable energy source and improving the energy independency.